Serum Vitamin D Level in Patients with Coronary Artery Disease and Association with Sun Exposure: Experience from a Tertiary Care, Teaching Hospital in India. (3rd February 2019) - Akhtar, Tauseef; Aggarwal, Ramesh; Jain, Sachin Kumar
Abstract : Background . Vitamin D, a fat-soluble vitamin, has various extraskeletal effects, and several human and animal studies have suggested that vitamin D deficiency may be a contributory factor in the pathogenesis of coronary artery disease (CAD). However, such studies in the Indian subcontinent are either lacking or have shown conflicting results. Methods . This was a descriptive cross-sectional study involving 121 patients with CAD from a tertiary care center and their 80 age-matched healthy controls. Serum vitamin D levels along with serum and urine chemistries were measured in both the groups. The average duration of sun exposure/day and use of sunscreen were also considered in the study cohort using a questionnaire. Serum vitamin D levels were categorized into deficient (<30 nmol/lit), insufficient (30–75 nmol/lit), and sufficient (>75 nmol/lit) groups. Results . Among the cases, 51.2% of the patients were vitamin D deficient and 44.6% patients had insufficient vitamin D levels, whereas among controls, 40% and 31% of the population had deficient and insufficient levels of vitamin D, respectively. However, the mean value of the serum vitamin D level was not statistically different in the cases as compared to that of the controls (34.06 vs 40.19 nmol/lit) (P = 0.08 ). Corrected serum calcium (9.26 vs 9.59 mg%) (P ≤ 0.0001 ) and serum albumin levels (4.21 vs 4.75 gm%) (P ≤ 0.0001 ) were lower in the cases than those of the controls. The average sun exposure/day was higher among the cases than that among the controls (2.93 vs 1.85 hours) (P = 0.001 ). Conclusion . Vitamin D deficiency is widely prevalent in Indian population despite abundant sunshine, and the duration of sun exposure is not correlated with serum vitamin D levels. Vitamin D deficiency is not associated with CAD. However, serum calcium is deficient in CAD patients as compared to the controls. Large-scale studies are required to explore the association further to evaluate the benefits of screening and correction of vitamin D deficiency in patients with CAD.